2000
DOI: 10.1002/(sici)1097-0223(200003)20:3<257::aid-pd781>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Choice of anticoagulant can influence the analysis using fluorescence in situ hybridization of fetal cells enriched from maternal blood

Abstract: A notable degree of research attention is being focused on the use of fetal cells enriched from the blood of pregnant women as a non-invasive means of prenatal diagnosis. By using magnetic activated cells sorting (MACS) and fluorescence in situ hybridization (FISH), we have examined the efficacy of enriched fetal cells in determining fetal sex. An unexpected finding of this investigation was that the sensitivity of this analysis was influenced by the anticoagulant used to treat the maternal blood samples. As s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On the basis of previously published literature, it has been shown that the use of heparin yield poorer results in the isolation of fetal cells as compared to EDTA. Heparin treated samples showed lower detection rates and hence EDTA instead of heparin was used as the anticoagulant for the blood samples in our study (8).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of previously published literature, it has been shown that the use of heparin yield poorer results in the isolation of fetal cells as compared to EDTA. Heparin treated samples showed lower detection rates and hence EDTA instead of heparin was used as the anticoagulant for the blood samples in our study (8).…”
Section: Discussionmentioning
confidence: 99%
“…Eiben found that 3.6 % of amniotic fluid cell preparations from karyotypically normal pregnancies showed aneuploidy in 10-60 % of the scored cells. 109 A further limitation of FISH is that it can only test for certain chromosomal abnormalities. By using strict criteria for scoring interphase FISH, no abnormal cases were actually missed and no inappropriate diagnoses were made.…”
Section: Cell Analysismentioning
confidence: 99%
“…104 Of the truly trisomic pregnancies, 11-13 % of the cell nuclei scored had only 2 signals. 108−110 Factors influencing the hybridisation efficiency of FISH probes include the method of cell preparation and fixation 9,10,42,111 the type of anticoagulant used, 109 the method of fetal cell sorting 112 and the inherent properties of the FISH probes themselves. Unfortunately, very few cell sorting systems have produced yields even approaching 30-50 cells.…”
Section: Cell Analysismentioning
confidence: 99%